Virtual Entity-Based Rapid Prototype for Design and Simulation of Humanoid Robots. (15th July 2013) - Tong, Guofeng; Gu, Jiuhong; Xie, Wei
This paper proposes a framework for a virtual entity-based rapid prototype (VERP) to facilitate the design and simulation of humanoid robots. The VERP framework consists of three components: virtual entities, a high-fidelity simulation environment with physical and rendering engines, and an interface between the physical and simulation environments. To study the effectiveness of the proposed framework, we present a complete prototype for a humanoid robot using virtual entity modelling, control algorithm design and simulation. The humanoid robot is mathematically modelled with adjustable physical parameters which determine the kinematic and dynamic behaviour of the virtual entity in the simulation environment. With the simulated model, a control scheme for the virtual entity and the actual humanoid robot are designed and implemented through the interface. The empirical experiments and numerical analysis show the effectiveness and preciseness of the proposed VERP in terms of simulation fidelity, dynamic performance, and control interface.